Real world drug treatment models for pregnancy complicated with urinary tract infection in China from 2018 to 2022: a cross-section analysis - Jin, Jing; Li, Changyan; He, Yuqing; Pan, Jiaqian; Zhu, JiaLei; Tang, Jing (Frontiers in Pharmacology, 2024)
objective: Urinary tract infection (UTI) is common in pregnant women. The selection of anti-infection plans during pregnancy must take into account the dual factors of patient pregnancy status and urinary tract infection anti-infection treatment, as well as the efficacy, cost, risk, and potential adverse reactions associated with each method applied to individual patients.Our objective is to investigate the actual drug treatment patterns of UTI patients during pregnancy in China over the past five years, with a particular emphasis on the trend and rationality of antibiotic use in these patients over the past five years. Method: We conducted a cross-sectional analysis of data from a China Medical Association-supervised hospital prescription analysis cooperation initiative. From January 2018 to December 2022, the information is extracted from prescriptions/medical orders of patients with UTI during pregnancy. Results: Among the 563 patients included in this research, Chengdu (36.59%), Guangzhou (27.72%), and Shanghai (8.70%) were the top three cities. Over the course of five years, the average age was 29.60%± 6.59 years. Each patient's primary anti-infection medications were statistically analyzed. Cephalosporins (403), enzyme inhibitors (66), and penicillins (34) were the first few categories, followed by the most commonly used cephalosporins. Cefuroxime, ceftriaxone, and cefdinib, rounded out the top five. Cefoxitin and cefaclor. According to the five-year change in dosage, cephalosporins have always ranked first. Three of the top five most expensive drugs are cephalosporins, carbapenems, and enzyme inhibitors. Conclusion: The average age of patients who visit a doctor has not increased substantially, but the opportunity cost of female fertility has increased. The selection of medications is generally reasonable, and the dosage of the first-line cephalosporins recommended by the guidelines is relatively high. The dosage of furantoin and fosfomycin, which are more prevalent in urinary tract infections, is however relatively low. In addition, some expensive pharmaceuticals may increase patients' financial burden. On the premise of meeting clinical needs, future research will focus on how to further improve the level of rational drug use in outpatient clinics, attain economical, safe, and effective drug use, and thus reduce the economic burden on patients.